Robertson's book of firsts : who did what for the first time - Robertson, Patrick, 1940; Robertson, Patrick (New York : Bloomsbury, 2011)
"The one-of-a-kind encyclopedia of the first time for everything, from advertisements to zippers."--Jacket.
Includes index.
Keywords: Curiosities and wonders -- Encyclopedias; Curiosities and wonders -- United States -- Encyclopedias; Handbooks, vade-mecums, etc